Neoliberal rhetorics and body politics : plastinate exhibits as infiltration - Pauliny, Tara (Cultural studies/pedagogy/activism., 2016)
Articulating how the plastinate exhibits BODY WORLDS and BODIES ... The Exhibition offer tangible and rich sites within which to understand neoliberalism's impact beyond the purview of public policy, this book identifies the rhetorical mechanisms and methodologies that propel neoliberalism's travel. Focusing its analysis on the shows' rhetorical deployment of necropolitics, biopolitics, intimacy, and affect, it illustrates how a pop-cultural artifact can both reach individual viewers and reflect the transnational and neoliberal relationship between nation-states.